Fiber optic temperature sensor based on No-Core Fiber (NCF) for high temperature sensing - Mohamed, Norhafniza (2019)
This paper proposes an improved fiber optic temperature sensor based on No- Core-Fiber (NCF) with sol-gel coating material for high temperature sensing. The main advantage of this sensor is the multimode interference (MMI) effect could react better to the changes of its surrounding compared with the multimode fiber. Without a physical cladding, an NCF will consider its surrounding as the cladding layer that facilitates the total internal reflection of the propagated light wave. With that configuration, changes of surrounding refractive index will impact the MMI effect directly. The design of sensor using Rsoft Beam Prop software has been carried out to determine the power intensity and temperature sensitivity. In addition, three different sol-gel materials were used to evaluate the sensor performance. From the simulation result, compared to TiO2 and SiNx, it is found that the ZrO2 coating has most significant performance in enhancing seven time greater than without coating within temperature range of 25 °C to 100 °C. The temperature sensitivity became 0.01637 dB/°C rather than 0.0225 dB/°C. Therefore, the sensor with ZrO2 is the most suitable for monitoring the high-temperature sensing applications.